Efektivitas Booklet Elektronik Berbasis Problem-Based Learning Terhadap Minat Belajar dan Berpikir Kritis Peserta Didik - Pujiati TM, Indah; Octavia, Bernadetta (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the effect of an electronic booklet based on problem-based learning on students’ learning interest and critical thinking skills. The method used was a quasi-experimental design with a pretest-posttest control group design. The research was conducted from August to September 2025 in grade XI of SMAN 1 Ngemplak. The sampling technique used random sampling, resulting in class XI F1 as the experimental class and XI F3 as the control class, with a total of 72 students. Data were collected using a learning interest questionnaire and a critical thinking test. Data analysis was performed using MANOVA with the assistance of SPSS version 22. The results showed that the use of a problem-based learning-based electronic booklet had an effect on students’ learning interest and critical thinking skills simultaneously. In conclusion, the use of a problem-based learning-based electronic booklet improves students’ learning interest and critical thinking skills compared to conventional learning. Keywords: Effectiveness, Electronic Booklet, Problem-Based Learning